Analysis of the Legends of the Special Region of Yogyakarta as a Source of Character Values Based on Thomas Lickona's Theory - Khalifatun Saudah; Muhammad Saleh; Hajrah Hajrah; Usman Usman (Journal of Educational Sciences, 2026)
This study aims to analyze the character values embedded in the legends of the Special Region of Yogyakarta based on Thomas Lickona’s character theory. Folklore, especially legends, plays an essential role as a medium of character education because it conveys moral messages, ethics, and local wisdom relevant to young generations. The research employed a descriptive qualitative method with content analysis of twelve legends compiled in Dhanu Priyo Prabowo’s Anthology of Folklore of the Special Region of Yogyakarta. The findings reveal that each legend contains character values categorized into Lickona’s three dimensions: moral knowing, moral feeling, and moral action. These values include loyalty, religiosity, hard work, sacrifice, solidarity, environmental awareness, and integrity. Furthermore, the results are in line with the five core values of Indonesia’s Strengthening Character Education program (PPK), namely religious, nationalist, independent, cooperative, and integrity. Therefore, Yogyakarta’s legends can serve as contextual learning resources in language, literature, and character education, while simultaneously contributing to the preservation of local wisdom.